Sustainable Camping Practices Among Malaysian Youth - Usolludin, Hazi Hafizah (IIUM PRESS, 2025)
Camping has become increasingly popular among Malaysian youth; however, its environmental consequences, including soil erosion, wildlife disturbance, and pollution, remain underexplored. This study investigates the relationship between youth campers’ travel behaviour, conservation practices, and environmental impacts. Employing a quantitative approach, data were collected via structured online questionnaires from 159 Malaysian campers aged 18–30. Descriptive statistics and Pearson’s correlation analysis revealed a strongly positive relationship between youth campers' travel behaviour and environmental degradation (p < .001), with campers’ preferences emerging as the most influential factor (r=0.913). In stark contrast, campsite conservation practices exhibited a very weak positive correlation (p<.001). These findings highlight the critical need for targeted educational campaigns and policy measures focused on behaviour-driven strategies to promote sustainable camping practices and mitigate ecological harm. The study adds to the ecotourism literature by highlighting the dominance of individual choices over management practices in determining environmental outcomes.